PERILAKU ALTRUISTIK PADA MASYARAKAT TERDAMPAK BENCANA BANJIR DI KELURAHAN PEDURENAN, KECAMATAN KARANG TENGAH, KOTA TANGERANG - Hasrian, H; Bimantara, M. Aji; Rezi, M. Syahrul; Rahman, Fathin Aulia (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
Indonesia faces a high risk of natural disasters, one of which is flooding, particularly in lowland areas. This study aims to analyze the altruistic behavior and resilience of communities affected by floods in Pedurenan Sub-district, Karang Tengah District, Tangerang City, Banten. The research employs a quantitative method with a percentage descriptive approach using a Likert Scale to measure levels of altruism. The findings reveal that the majority of the community (63%) demonstrates a moderate level of altruism, with significant contributions from younger age groups and low-income residents. Social solidarity is evident in collective actions during disasters, such as assisting with evacuation and providing basic necessities. Altruistic behavior is influenced by various factors, including age, income level, and length of residency. These findings offer recommendations to enhance community capacity in disaster response through strengthened solidarity and improved social management.